Health and Wellbeing in Late Life Perspectives and Narratives from India - Chatterjee, Prasun (Springer Nature Singapore : Imprint: Springer, 2019)
This open access book takes a multidisciplinary approach to provide a holistic understanding of late old age, and situates the aged person within the context of family, caregivers, clinical and other institutions. All through the book, the author discusses preparedness for an aging individual as well as the society in the Indian context. The book highlights inevitable but mostly neglected health issues like depression, dementia, fall, and frailty and provides detailed analyses of solutions that are practicable in low resource settings. It also brings up intergenerational differences and harmony in the context of holistic care of older Indians. Alongside clinical perspectives, the book uses narratives of elderly patients to dwell on the myriad of problems and issues that constitute old age healthcare. Demonstrating cases that range from the most influential to the most underprivileged elderly in India, the book enlightens multiple caregivers-doctors, nurses, and professional caregivers, but also family members-about the dynamic approach required in dealing with complex issues related to late old age. The narratives make the book relatable and interesting to non-academic readers, with important lessons for gerontological and geriatric caregiving. It is also of use to older adults in preparing for active aging. .